2019
DOI: 10.1002/ese3.353
|View full text |Cite
|
Sign up to set email alerts
|

Gas production from a silty hydrate reservoir in the South China Sea using hydraulic fracturing: A numerical simulation

Abstract: The low permeability of silty hydrate reservoirs in the South China Sea is a critical issue that threatens safe, efficient, and long‐term gas production from these reservoirs. Hydraulic fracturing is a potentially promising stimulation technology for such low‐permeability reservoirs. Here, we assess the gas production potential of a depressurization horizontal well that is assisted by the hydraulic fracturing using numerical simulation according to field data at site SH2 in this area. In addition, the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 80 publications
(134 reference statements)
0
61
0
Order By: Relevance
“…They concluded that the permeability improvement, which raised the average gas production rate by one order of magnitude, might be more reliable than the aggressive depressurization on the gas recovery enhancement. Hence, enhancing the permeability to assist depressurization is necessary [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the permeability improvement, which raised the average gas production rate by one order of magnitude, might be more reliable than the aggressive depressurization on the gas recovery enhancement. Hence, enhancing the permeability to assist depressurization is necessary [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas hydrate (NGH) is regarded as one of the most promising alternative energy resources that is widely distributed in permafrost zones and oceanic sediments. The NGH reservoirs are generally divided into four classes: Class 1 (the free gas layer above which the hydrate-bearing layer exists), 1 Class 2 (hydrate formation overlies a mobile water zone), 2 Class 3 (only one hydrate formation without any underlying zone of mobile fluids), 3,4 and Class 4 (reservoirs with low hydrate saturation and unconfined geological strata near the seafloor, hydrates in fractures, etc). 5 The percentages of the above four types of reservoirs in nature are expected to be 14%, 5%, 6%, and 75%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This temperature change will dramatically affect the efficiency of hydrate production [27,28]. It may conduct the wellbore instability, sand production ( Figure 2), and methane leakage [26,[29][30][31]. The temperature range of hydrate layers in Messoyakha gas field, Mount Elbert gas hydrate well (Alaska), Malik gas hydrate site (Canada), and Qinghai-Tibet Plateau were about 8~11°C [32], -8~10°C [33,34], -20~-1°C [6,12,33], and -0.1~-5°C [35], respectively, which are different from the traditional petroleum temperature.…”
Section: Introductionmentioning
confidence: 99%